1998
DOI: 10.1021/jf980006w
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Heat-Induced Soy Protein Gels As Affected by Ionic Strength and pH

Abstract: Hydration properties of acidic soy protein gels, prepared with different salt solutions, were studied. The type of bonds that stabilize gel structure and the nature of protein species that make up and stabilize such structure were also investigated. The microstructure of gels was evaluated by scanning electron microscopy (SEM) and water-holding capacity (WHC) assays. The stability and nature of protein fractions of gel matrices were analyzed by solubility measurements and sodium dodecyl sulfate−polyacrylamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 21 publications
7
66
0
Order By: Relevance
“…The thermal properties of MTGase-induced gels of soy proteins (including glycinin-rich and -conglycinin-rich SPIs) were evidently diVerent from that of heat-induced gels. In the heat-induced gelation of soy proteins, the protein denaturation induced by heat treatment is often a prerequisite for gel formation of soy proteins (van Kleef, 1986;Nakamura et al, 1986aNakamura et al, , 1986bPuppo and Añón, 1998;Renkema & Vliet, 2002a,b;Kinesella, 1985a, 1985b), since the exposed hydrophobic areas of denatured proteins can interact and aggregate to form gel-network upon cooling. In this case, the soy protein gels were completely thermoreversible at pH 3.8 or 5.2, and the gel strength declined after reheating-recooling cycle at pH 7.6 (Renkema et al, 2002b).…”
Section: Substrate Proteinmentioning
confidence: 99%
“…The thermal properties of MTGase-induced gels of soy proteins (including glycinin-rich and -conglycinin-rich SPIs) were evidently diVerent from that of heat-induced gels. In the heat-induced gelation of soy proteins, the protein denaturation induced by heat treatment is often a prerequisite for gel formation of soy proteins (van Kleef, 1986;Nakamura et al, 1986aNakamura et al, , 1986bPuppo and Añón, 1998;Renkema & Vliet, 2002a,b;Kinesella, 1985a, 1985b), since the exposed hydrophobic areas of denatured proteins can interact and aggregate to form gel-network upon cooling. In this case, the soy protein gels were completely thermoreversible at pH 3.8 or 5.2, and the gel strength declined after reheating-recooling cycle at pH 7.6 (Renkema et al, 2002b).…”
Section: Substrate Proteinmentioning
confidence: 99%
“…If heating is performed on acidified systems (pH <3.5) acidic gels are stabilized mainly by non-covalent interactions. On the other hand, heating at neutral pH causes disulfide bridging, and the covalent interactions between the various soybean protein subunits (especially the acidic and basic subunits of 11S) strengthen the gel structure (Puppo & Anon, 1998;Puppo, Lupano, & Anon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its various physical functions, including gelation, viscosity, emulsification and foaming, (Kohyama et al, 1995, Nagano et al, 1996Puppo and Anon, 1998), soybean protein (SP) has generally been used in fabricated food products such as frozen tofu, ganmodoki, sausages, bacon, and many meatlike products (Adler-Nissen and Olsen, 1979;Smith and Circle, 1980: Parks andCarpenter, 1987). It has been also reported that soybean milk is coagulated by some proteinases (Fuke et al, 1985;Yasuda et al, 1999, Aoyama et al, 2000.…”
Section: Introductionmentioning
confidence: 99%